(untitled) (Baghdad Science Journal, 2025)
Simple, sensitive and economical spectrophotometric methods have been developed for the determination of cefixime in pure form. This method is based on the reaction of cefixime as n-electron donor with chloranil to give highly colored complex in ethanol which is absorb maximally at 550 nm. Beer’s law is obeyed in the concentration ranges 5-250 µg ml-1 with high apparent molar absorptivities of 1.52×103 L.mole-1. cm-1.